Change of Meteorological Values in Autumn of Samarkand Region - G.Kh. , Kholbaev; Kh. T. , Egamberdiev; H.Kh. , Egamberdiev (International Journal of Psychosocial Rehabilitation, 2020)
This work shows a map of the location of meteorological stations and posts in the Samarkand region. In autumn, the average air and soil temperature change at the regional stations over the months, the dates of different air temperature transitions, and the average air and soil temperature values over five days were calculated. Average temperature values for the baseline and current climatic periods are analyzed.